Catalytic cyclization of propargyl bromoethers via electrogenerated nickel(I) tetramethylcyclam in Ionic liquids: water effects - Mendes, Jorge António Silva (2019)
Cyclic voltammetry and controlled-potential electrolysis have been employed to investigate the reductive intramolecular cyclization of propargyl bromoethers derivatives, catalyzed by electrogenerated (1,4,8,11-tetramethyl-1,4,8,11-tetraaza-cyclotetradecane) nickel(I), [Ni(tmc)](+), as the catalyst, in N,N,N-trimethyl-N-(2-hydroxyethyl) ammonium bis(trifluoromethylsulfonyl) imide, [N-1 1 1 2(OH)][NTf2] and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide, [C(2)mim][NTf2] in the absence and in the presence of water. The results show that the reaction leads to the formation of the expected heterocyclic compounds, in moderate to good yields. These compounds are important intermediates in the synthesis of natural products with possible biological activities.